I love birds! : 52 ways to wonder, wander, and explore birds with kids - Ward, Jennifer, 1963- (Roost Books, 2019)
"Part journal, part field guide, I love birds! is chock-full of the activities, information, and rich resources that will fuel discovery and inspire families, urban and rural, with everything bird. Through sensory, hands-on, creative explorations that involve birding basics and the how's and why's of bird behavior, parents are invited share the joy of birds with children ages 4 to 8. The activities here will engage children's imagination and sense of wonder as they observe birds in the wild, become citizen scientists, delve into their DIY and artistic side, and enjoy the simple bounty of bliss birds provided merely by engaging with them--all the while forging a deeper understanding, appreciation, and stewardship toward nature, our planet, and all things feathery."--